2023
DOI: 10.1007/s11136-023-03386-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual quality of life in young gynaecological cancer survivors: a qualitative study

Abstract: Purpose The impact of cancer diagnosis and treatment on sexual quality of life (SQoL) is a significant and often neglected issue in the treatment and survivorship period of young gynaecological cancer survivors (YGCS). This study sought to explore women’s lived experiences to understand how to protect and improve SQoL. Methods A qualitative study with women aged 18–45 and pre- or perimenopausal at diagnosis (n = 15). A thematic analysis was performed in NV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previous research has shown that nurses are considered good communication partners regarding sexuality (Roussin et al, 2023). To receive information and talk about challenges is experienced to help allay concerns about sexual life and manage sexual problems (Chow et al, 2016), something that was experienced by the women in this study.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Previous research has shown that nurses are considered good communication partners regarding sexuality (Roussin et al, 2023). To receive information and talk about challenges is experienced to help allay concerns about sexual life and manage sexual problems (Chow et al, 2016), something that was experienced by the women in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Even though the women in our study expressed a conscious awareness of not pressuring themselves into unwanted sexual activity, the guilt for rejecting their partners' sexual needs simultaneously put their own need for closeness at stake. Previous studies confirm that women experience guilt when they have difficulties engaging in sexual activity following gynaecological cancer (Roussin et al, 2021(Roussin et al, , 2023Vermeer et al, 2016). Unfortunately, having sex as an obligation can deprive women of sexual enjoyment and is associated with negative sexual and relational outcomes (Georgieva et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations